Evaluation of Cost and Time Performance Using The Earned Value Management Method in Hospital Building Construction Projects - Putu Eny Suhardiyani; I Putu Widyarsana; Putu Riska Wulandari (Devotion : Journal of Research and Community Service, 2026)
The construction sector currently faces increasingly dynamic challenges, particularly in healthcare infrastructure development, which requires high standards of functionality and timeliness. This study aims to evaluate the effectiveness of project management through cost and schedule performance analysis using the Earned Value Management (EVM) method on a hospital building construction project. The research approach used is descriptive evaluative, analyzing three main variables: Budgeted Cost Work (BCC), and Cost of Goods and Services (CW). Schedule (BCWS), Budgeted Cost Work Performed (BCWP), and Actual Cost Work Performed (ACWP). Results study disclose existence difference significant between achievements financial and time effectiveness. In terms of schedule, the project experienced a projected deviation resulting in a delay of 60 calendar days from the initial contract duration of 360 days. However, financially, the project management has successfully demonstrated very efficient performance. This project is projected to achieve cost savings of Rp. 718,520,400.00 with a total estimated final cost (EAC) of Rp. 38,731,479,600.00 from a total contract value of Rp. 39,450,000,000.00 billion. These results confirm that the implementation of a strict cost control system is able to produce positive budget optimization for the project owner despite facing constraints on the work time aspect.